Reformasi Pajak Berbasis Keadilan dan Kepastian Hukum: Strategi Efektif Mengurangi Sengketa Pajak dan Meningkatkan Efisiensi Sistem Perpajakan - Dwi Ramadhan, Wanda; Nausta Pardede, Tiolina Evi (Politeknik Keuangan Negara STAN, 2025)
An efficient, fair, and legally certain tax system is a key element in supporting a country's economic stability. However, Indonesia faces significant challenges in managing its tax system, particularly with the increasing number of tax disputes brought to the Tax Court and the Supreme Court. This study aims to analyze the factors contributing to the high number of tax disputes and evaluate strategies that can be implemented to create a more efficient and fair tax system. This research employs a qualitative literature review method, analyzing various academic literature, tax regulations, and statistical data from the Directorate General of Taxes (DGT) systematically. The findings indicate that complex tax regulations, inconsistent rule interpretations, and a lack of transparency in tax audit processes are the primary causes of the high volume of tax disputes. Furthermore, this study finds that the level of digitalization in tax administration remains suboptimal, contributing to increased errors in tax reporting and auditing. In terms of policy implications, this study recommends simplifying tax regulations, enhancing tax administration capacity through digitalization, and improving taxpayer education and outreach. Additionally, increasing efficiency in tax dispute resolution through mediation and arbitration is proposed as a solution to reduce the burden on tax courts. With more targeted reforms, Indonesia’s tax system is expected to become more transparent, efficient, and equitable for all taxpayers.